Legality of Taking pictures during Criminal Investigations in Algerian Legislation - MAAMERI , Abderrachid; MAAMERI, Mohamed; BAHRI, Bouzid (Journal of Human Sciences, 2025)
This article discusses the act of taking pictures as one of the contemporary, unique, and remarkable measures in the realm of inquiry into crimes and severe transgressions against society and the legal system. It aims to uncover the truth about these crimes and their perpetrators. The legislator has regulated its provisions under Law No. 06-22 dated 20/12/2006, amending and supplementing the Code of Criminal Procedure, in accordance with the advancements experienced by the international community in the field of crime prevention and detection. This is achieved through the use of modern and technological means, particularly highlighting the legality of this procedure and the formal and objective conditions required for its validity in Algerian legislation, for its admissibility along with the evidence obtained from it.